Applying the termination of resuscitation rules to out-of-hospital cardiac arrests of both cardiac and non-cardiac etiologies: a prospective cohort study. Issue 1 (December 2016) - Kashiura, Masahiro; Hamabe, Yuichi; Akashi, Akiko; Sakurai, Atsushi; Tahara, Yoshio; Yonemoto, Naohiro; Nagao, Ken; Yaguchi, Arino; Morimura, Naoto
Abstract Background The 2015 American Heart Association Guidelines for Cardiopulmonary Resuscitation recommend Basic Life Support (BLS) and Advanced Life Support (ALS) rules for termination of resuscitation (TOR). However, it is unclear whether the TOR rules are valid for out-of-hospital cardiac arrests (OHCAs) of both cardiac and non-cardiac etiologies. In this study, we validated the TOR rules for OHCA resulting from both etiologies. Methods This was a prospective multicenter observational study of OHCA patients transported to 67 emergency hospitals between January 2012 and March 2013 in the Kanto region of Japan. We calculated the specificity and positive predictive value (PPV) for neurologically unfavorable outcomes at one month in patients with OHCA of cardiac and non-cardiac etiologies. Results Of 11, 505 eligible cases, 6, 138 and 5, 367 cases were of cardiac and non-cardiac etiology, respectively. BLS was performed on 2, 818 and 2, 606 patients with OHCA of cardiac and non-cardiac etiology, respectively. ALS was performed on 3, 320 and 2, 761 patients with OHCA of cardiac and non-cardiac etiology, respectively. The diagnostic accuracy of the TOR rules for predicting unfavorable outcomes in patients with OHCA of cardiac etiology who received BLS included a specificity of 0.985 (95 % confidence interval [CI]: 0.956–0.997) and a PPV of 0.999 (95 % CI: 0.996–1.000). In patients with OHCA from cardiac etiologies who received ALS, the TOR rules had a specificity of 0.963 (95 % CI: 0.896–0.992) and a PPV of 0.997 (95 % CI: 0.991–0.999). In patients with OHCA from non-cardiac etiologies who received BLS, the specificity was 0.915 (95 % CI: 0.796–0.976) and PPV was 0.998 (95 % CI: 0.995–0.999). For patients with OHCA from non-cardiac etiologies who received ALS, the specificity was 0.833 (95 % CI: 0.586–0.964) and PPV was 0.996 (95 % CI: 0.988–0.999). Conclusions Both TOR rules have high specificity and PPV in patients with OHCA from cardiac etiologies. For patients with OHCA from non-cardiac etiologies, the rules had a high PPV, but relatively low specificity. Therefore, TOR rules are useful in patients with OHCA from cardiac etiologies, but should be applied with caution to patients with OHCA from non-cardiac etiologies.